Depictions of activism at universities compared; Contexts for Political Engagement - Ocan, Johnson (International Journal of English Literature and Social Sciences, 2025)
The goal of this study is to make a case that the campus of a university served as the venue for discussion, plan-ning, and mobilization. Campuses have come to represent the perfect arena of power where social demands are made and power battles are fought since they serve as a microcosm of society. The campus acted as both a micro-cosm of the outside world and a testing ground for ideas and activities before they were introduced to the entire public. In terms of approach the study used a documentary review to highlight the various experiences associated with student activism from three public universities in Uganda. Findings indicate that, the university has devel-oped into a setting for remaking society. The youth of Uganda in the 1990s sparked significant social transfor-mation and began a new chapter in human history. The movement stressed the significant position that higher ed-ucation institutions hold as centers of research, teaching, and community action. Since the freedom of thinking expressed inside the campus's physical seting gives humanity the vital inventiveness required to create a better and fairer world, the campus' privileged status should continue to be maintained. The study only included three public universities in Uganda, so it may not be feasible to extrapolate the results to other nations. Instead, it may be more practical to provide students with tailored learning support, let alone allow the university to grow organ-ically.